A Case of Tuberculous Peritonitis Accompanied By Tuberculous Pleuritis - I Larasati A.Wahyu; Pramarta Y. Dwiputra (Publikasi Indonesia, 2024)
Tuberculous peritonitis is a form of extrapulmonary tuberculosis, a peritoneal or visceral inflammation caused by Mycobacterium tuberculosis. The disease is rarely independent but is usually a continuation of the tuberculosis process elsewhere, especially pulmonary tuberculosis. We report a case of TB peritonitis accompanied by TB pleurisy, a 29-year-old female patient with complaints of an enlarged abdomen, heartburn, fever, diarrhoea, and decreased appetite. Treatment history was Acitral, Zinc, and Metronidazole. On physical examination, it was found that the general condition was weak, and the axilla temperature was 39.5ºC. Thorax examination: decreased vesicular sound on the left chest. Abdominal examination found distension, epigastric tenderness, undulation, shifting dullness, checkerboard phenomenon, and increased bowel noise. Laboratory examination of complete blood within normal limits. Complete stool; yellow color, mucus (+), leukocytes 4-6/LPB, bacteria (+). The thorax photo showed left pleural effusion, BOF 3 position: ascites. Abdominal ultrasound results: thickening of the peritoneum, ascites, suspected TB peritonitis. Results of ascites and pleural fluid analysis: rivalta (+) and Adenosine Deaminase (ADA) increased. From anamnesis, physical examination and supporting examination can be established to diagnose TB peritonitis and TB pleuritis, followed by OAT therapy and FDC for 12 months. From this case, it can be concluded that clinical and supporting examinations (radiology) are needed to diagnose correctly, and body fluid analysis examinations can help confirm the diagnosis.